Checklist of the endemic vascular plants of Paraguay - Peña Chocarro, María Del Carmen; de Egea, Juana (Phytotaxa, 2018)
We present a list of endemic plants of Paraguay, which includes 374 taxa from 52 families and 162 genera based on the revision of primary data (herbarium collections). Synonyms, habit, distribution in Paraguay and all the voucher specimens seen or cited in recent bibliographies or in the consulted databases are provided for each taxon. A brief analysis of the diversity and importance of this endemic flora is presented. A list of excluded species, which were considered as endemics in previous publications, is also included.